Ford Prefect or Volkswagen Golf? On the Differences in the Polish and Belarusian Translations of The Hitchhiker’s Guide to the Galaxy - Angelika Peljak ([sic])
This paper takes a relevance-theoretical approach to Douglas Adams’ The Hitchhiker’s Guide to the Galaxy in the Polish (Banaszak) and Belarusian (Kaściukievič) translation. The study treats translation as aiming for the optimal balance between the processing effort required of the reader, and the positive cognitive effect achieved, or, put differently, as fulfilling Gutt’s communicability condition. In doing so, this paper indicates how vastly different outcomes are achieved depending on the translator’s attitude and the choices one makes. The analysis includes a discussion of various elements of the novel, such as proper nouns, names of elements of the fantastic world, and cultural elements. The study reveals that Kaściukievič embedded his translation in the target culture more than the original was in the source culture, and thus achieved the communicability condition; on the other hand, Banaszak retained most of the cultural features of the original, which made her translation less relevant for the Polish reader.